Performance investigation and mass transfer enhancement of a novel cone-type solar seawater still - Yang, Jie; Chang, Zehui; Zhang, Xin; Zhu, Guopeng (Frontiers in Energy Research, 2023)
There are some disadvantages in the operating process of the basin solar seawater still (BSSS), such as long mass transfer distance, large heat indolence, huge floor space, and poor bearing pressure ability. A novel cone-type solar seawater still (CTSSS) is presented to overcome the weaknesses of the BSSS in this study. The CTSSS has the characteristics of seawater liquid film evaporation, short mass transfer distance, the condensation sleeve is parallel to and above the evaporation sleeve, and the condensation area is larger than the evaporation area. In order to clarify the performance of the CTSSS, the influence mechanism of feed seawater mass flow rate, heating power and heating temperature on the fresh water yield of the CTSSS was analyzed, the method of enhancing the mass transfer of the binary mixed gas in the CTSSS was explored, and the law of heat and mass transfer of the binary mixed gas in the annular enclosed small space was investigated. The results indicated that the maximum fresh water yield of the CTSSS is 62.7 g/20 min at the feed seawater mass flow rate of 400 g/h when the input power is 200 W, which is 4.5% higher than that when the feed seawater mass flow rate is 300 g/h. The performance ratio (PR) of the CTSSS is increased as the heating power, the PR of the CTSSS is 0.65 when 180 W heating power is employed. The steady state fresh water yield of the CTSSS with mirror condensation sleeve at 85°C is 84.6 g/20 min, which is 12.1% higher than that with non-mirror condensation sleeve Compared with the CTSSS with non-mirror condensation sleeve, the value of proportions of radiative heat transfer in the total heat transfer of the CTSSS with mirror condensation sleeve decreased by 6.6%, and the value of proportions of evaporative heat transfer increased by 6.4%. This study would provide a reference for small-scale decentralized application of solar desalination in remote areas.